The debate on growing inequality: Implications for developing countries and international - Jürgen K. Zattler (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2015)
A body of recent research is pointing to a growing inequality in many countries. The current debate focuses on high income countries. However, developing countries are an important element in understanding the full picture. First, evidence indicates that growing inequality can also be observed in many developing countries, in particular if top income and wealth evolution is taken into account, a phenomenon which is at variance with conventional economic theory. This has a multitude of economic, political and social implications for the respective countries. In particular, high inequality is linked with political instability, financial fragility and can undermine economic growth. Secondly, developing countries form an increasingly important part of the world economy. Therefore, options to combat inequality must take into account this broader picture. For any solution, one has to understand the driving forces behind growing inequality. Piketty's central claim is that the free-market system has a natural tendency towards increasing the concentration of wealth. However, there are strong arguments that ever growing inequality is not sustainable in the long-term, in particular because it would eventually slow down economic growth, increase debt levels as well as social and political instability. It is argued in this article that the tendency to accumulate capital at the top seems to lead periodically to unsustainable situations, whereby "external factors" such as wars, technological innovations, government re-distribution and bail-outs can rebalance (and have in fact in the past rebalanced) the system for some time. Governments of developing countries must act on two fronts to contain rising inequality: On the one hand, they have to scale-up domestic resource mobilisation in order to enhance social investments and re-distribution, as many Latin American countries did successfully in the last decade. On the other hand, they must foster the inclusiveness and resilience of their development strategies. Correspondingly, development institutions should go beyond their current focus on extreme poverty and take into account inequality - in terms of general approaches, country support and strategies as well as instruments. Finally, the issue should be adequately taken up within the new "Post-2015" framework.
Keywords: E21; E24; H20; O20; 330; inequality; financial stability; developing countries